‘Evaluation of occupational and nonoccupational interstitial lung disease in railway workers’ - Islam M Mostafa; Gamal Salem; Maryam A. A. Kader; Dina Ruby (Egyptian Journal of Chest Disease and Tuberculosis, 2024)
Introduction Occupational lung diseases include a wide variety of respiratory diseases with clinical manifestations and diagnostic test results that have features similar to nonoccupational diseases.